FIRST ASSAY OF PHOTO-IDENTIFICATION IN MARINE TURTLES’ NESTING POPULATION/ Primer ensayo de la foto-identificación en una población anidadora de tortugas marinas - Yoandy Almaguer Valdés; Julia Azanza Ricardo; Fernando Bretos Trelles; Olga Espada Abad (Revista de Investigaciones Marinas, 2014)
Guanahacabibes, the westernmost part of Cuba, contains important habitat for many terrestrial and marine species, particularly marine turtles. Previous studies of turtles in this area have focused on biological characteristics such as re-migration patterns, nesting patterns, and different abiotic factors such as temperature and meteorological phenomena, which determine the fate of individuals in this population. Traditional techniques for individual identification can cause stress to the animals, however, and have a limited duration. For this reason, a study was conducted to establish the efficacy of photo-identification of morphological characters as less stressful and longer-lasting means o individual turtle identification. Of 1032 tagged individuals only 140 have been photoidentified, 135 were green turtle (Chelonia mydas) and five were loggerhead turtle (Caretta caretta). Normality and homogeneity of variance was determined for all quantitative variables. Bifactorial ANOVA were determined if there was a difference in the number of vertices of post-orbital scales over years, beaches and the interaction of the two factors. StudentNewman-Keuls was used for multiple comparison test. Errors made up only 0.71% of the photos analyzed (200 in total). The number of vertices of post-orbital scales showed no difference among years or beaches with a predominance of pentagonal scales. The coding used here for animal identification using a numerical sequence proved feasible, with some failures, to help recognize and distinguish remigrating animals. Although photo-identification is not free of errors, the information it provides is very useful in conservation studies.